From Fear of Missing Out to Healthy Lifestyle: Understanding Motivation and Decision-Making in Padel Participation - Untung Eko Setyasari; Yanti Fadila Wahab; Anisa Desty Puspatriani; Rudi Kurniawan (Fakultas Ekonomi Universitas Garut, 2026)
Padel has rapidly emerged as one of the fastest-growing sports worldwide, including in Indonesia, where it has become increasingly associated with urban lifestyles, social interaction, and digital culture. This study aims to explore the motivations and decision-making processes underlying participation in padel, particularly in relation to healthy lifestyle orientation and Fear of Missing Out (FOMO). Using a qualitative case study approach, data were collected through in-depth interviews, observation, and documentation involving five participants from diverse occupational backgrounds. The data were analyzed thematically using Self-Determination Theory (SDT) and Consumer Behaviour Theory. The findings reveal that participation in padel is influenced by a combination of social, health, and lifestyle factors. FOMO, social media exposure, and peer influence serve as important triggers for initial participation, while sustained involvement is driven by enjoyment, health benefits, skill development, and social connectedness. The study also shows that participants gradually shift from externally driven motivations to more intrinsic forms of motivation. Furthermore, participation decisions are shaped not only by functional considerations but also by symbolic values related to identity, status, and social belonging. This study concludes that padel participation represents a dynamic interaction between FOMO, motivation, and behavioural decision-making, which may ultimately develop into a sustainable healthy lifestyle practice.